2006
DOI: 10.1007/s10336-006-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

Birds: blowin’ by the wind?

Abstract: Migration is a task that implies a route, a goal and a period of time. To achieve this task, it requires orientation abilities to find the goal and energy to cover the distance. Completing such a journey by flying through a moving airspace makes this relatively simple task rather complex. On the one hand birds have to avoid wind drift or have to compensate for displacements to reach the expected goal. On the other hand flight costs make up a large proportion of energy expenditure during migration and, conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
379
7
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(406 citation statements)
references
References 78 publications
15
379
7
5
Order By: Relevance
“…We found that wind conditions (head wind/tail wind and cross wind) en route were not related to the migration timing of the individual Russian and Svalbard geese, which is opposite to previous studies (Erni et al, 2005;Liechti, 2006;Pulido, 2007b). Wind parameters en route at the Russian flyway had high loading on PC3eR, but this PC was not selected by the model.…”
Section: En Routecontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that wind conditions (head wind/tail wind and cross wind) en route were not related to the migration timing of the individual Russian and Svalbard geese, which is opposite to previous studies (Erni et al, 2005;Liechti, 2006;Pulido, 2007b). Wind parameters en route at the Russian flyway had high loading on PC3eR, but this PC was not selected by the model.…”
Section: En Routecontrasting
confidence: 99%
“…Wind speed is probably the most important weatherrelated parameter determining flight speed and flight duration of birds (Erni et al, 2005;Liechti, 2006;Pulido, 2007b). Migrant birds can greatly increase their flight speed by responding appropriately to prevailing wind conditions (Newton, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Wind is treated as an important external factor in studies of large-scale seasonal migrations (33)(34)(35) and commuting flights (36-38) of seabirds. Although the migration patterns of seabirds associated with the large-scale wind systems are well documented (33)(34)(35), finer-scale movements in relation to variation of winds in scales of several minutes to hours are still unrevealed due to the lack of wind information relevant to the fine-scale movements of the seabirds. Using the methods outlined in this study, high-resolution wind information experienced by birds throughout their whole flight can be evaluated to investigate bird flight behavior in relation to more finescale turbulence and variation of wind.…”
Section: Bird-based Wind Covers Spatial and Temporal Observation Gapsmentioning
confidence: 99%
“…These conditions could also be associated with small-scale variations in heating that would favor the development of vigorous whirlwinds. Research in other areas has linked shifts in the flowering patterns of trees to El Niño events (Curran et al 1999) and shown that migratory birds often use the movements of fronts to provide them with tailwinds (Liechti 2006). …”
Section: Signsmentioning
confidence: 99%